Examining associations between oral cancer mortality and economic development of 13 European countries: an ecological and correlational study - Klára Boruzs; Eszter Barbara Bán; Viktor Dombrádi; Gábor Bányai; Gergő József Szőllősi; Klára Bíró (BMC Oral Health)
Abstract Background Cancer is a significant public health issue all over the world. The diagnosis, treatment and follow-up of cancer patients are a huge health, economic and social burden for societies. The link between the state of health of a country and its economic performance has been proven by numerous studies. The aim of this study was to examine the age-standardized death rate of oral cancer in relation to the economic development of 13 European countries. Methods Aggregated data were collected from the European Health for All (HFA-DB) database until 2019 and analysed using second degree polynomial functions and correlation analyses, followed by time-series analysis involving vector autoregressive models. Results We found that in 10 of the 13 surveyed countries, the age-standardized death rate of oral cancer initially increased with GDP growth and then showed a downward trend above a certain level of economic development. Austria had a weak but significant positive effect with the second lag of GDP, Hungary had a significant negative effect with the first lag of GDP, and Italy had a significant negative effect with the second lag of GDP. In most cases, both the first and second lags of GDP changes were not statistically significant, indicating that short-term fluctuations in GDP do not directly influence changes in oral cancer mortality rates. Overall, while there are clear long-term associations between GDP and oral cancer mortality rates, the immediate causal effects of GDP changes on mortality rates are limited, suggesting that other factors and longer-term dynamics could play a more crucial role in this relationship. Conclusions An increase in a country’s economic development alone does not guarantee a decrease in the number of oral cancer patients. Therefore, in order to reduce the number of cases of oral cancer, strengthening education and prevention are essential.